"Dots and lines": A melanonychia striata in regression: Report of a case. Issue 6 (2nd October 2017) - Burkink, Esther; Abdul Hamid, Myrurgia; Martens, Herm
Abstract: A 2‐year‐old Caucasian boy with melanonychia striata with multiple striking pits on the nail plate of one fingernail is described. Nail disorders often pose diagnostic and therapeutic challenges for clinicians, especially melanonychia striata, because of the fear of a subungual melanoma. Only a few childhood cases of melanonychia striata have been described, and the multiple pits are even less common. Dots distributed along melanotic lines is a finding referred to as "dots and lines" and can be a sign of regression of melanonychia in childeren.